Synchronous Metastasizing High-Grade Papillary Serous Carcinoma of the Fallopian Tube and Triple-Negative Primary Breast Cancer in a BRCA1 Mutation Carrier - Mihnea-Andrei Nicodin; Tudor-Petru Nicodin; Anca Popescu; Elena Rusu; Cosmin Alec Moldovan; Alice Elena Munteanu; Mariam Dalaty; Ovidiu Vasile Nicodin (Journal of Mind and Medical Sciences)
Patients with a BRCA1 germline mutation often represent a challenge for medical healthcare, since they develop malignancies that tend to be more aggressive and which need to be addressed in multidisciplinary teams with more individualized therapies. We report a case of a 37-year-old woman with a BRCA1 mutation who was diagnosed and treated for high-grade papillary serous carcinoma of the fallopian tube. Eight years later, her regular check-up imaging revealed a latero-aortic lymphadenopathy and a right breast tumor. She underwent a fine needle breast biopsy which was positive for invasive non-specific type carcinoma with negative estrogen, progesterone and Her2 receptors in immunohistochemistry tests. The patient underwent debulking surgery for metastatic lymphadenopathy, followed by chemotherapy with Carboplatin and Paclitaxel, and a modified right mastectomy with axillary lymphadenectomy. She subsequently initiated therapy with the PARP inhibitor Olaparib. No evidence of tumor recurrence was detected during the six-month postoperative follow-up period. The primary goal of this paper is to emphasize the complexity and challenges of managing patients with BRCA1 mutations who develop synchronous malignancies. This case report aims to highlight the increasing role of precision medicine and the importance of personalized, multidisciplinary therapeutic strategies, which include surgery, chemotherapy, and targeted therapies.